Impact of Carbon Dioxide on the Non-Catalytic Thermal Decomposition of Methane - Tobias Marquardt; Sebastian Wendt; Stephan Kabelac (ChemEngineering, 2021)
Economically and ecologically, the thermal decomposition of methane is a promising process for large scale hydrogen production. In this experimental study, the non-catalytic decomposition of methane in the presence of small amounts of carbon dioxide was analyzed. At large scales, natural gas or biomethane are possible feedstocks for the thermal decomposition and can obtain up to <semantics>5%</semantics> carbon dioxide. Gas recycling can increase the amount of secondary components even further. Experiments were conducted in a packed flow reactor at temperatures from 1250 to 1350 <semantics>K</semantics>. The residence time and the amounts of carbon dioxide and hydrogen in the feed were varied. A methane conversion of up to <semantics>55.4%</semantics> and a carbon dioxide conversion of up to <semantics>44.1%</semantics> were observed. At <semantics>1300 K</semantics> the hydrogen yield was <semantics>95%</semantics> for a feed of methane diluted in nitrogen. If carbon dioxide was added to the feed at up to a tenth with regard to the amount of supplied methane, the hydrogen yield was reduced to <semantics>85%</semantics>. Hydrogen in the feed decreases the reaction rate of the methane decomposition and increases the carbon dioxide conversion.